Educação ambiental “crítica-inovadora” no 3º ano do Ensino Fundamental: uma pesquisa do tipo intervenção pedagógica - Noal, Gabriela Rodrigues (2024)
This dissertation examines Environmental Education (EE) from a “critical-innovative” perspective, with the aim of transforming the educational sphere and the participating subjects to enable them to act in society in an ecological, civic, and emancipatory manner. The objective of this study was to analyze how a pedagogical intervention can facilitate and promote the integration of “critical-innovative” EE in primary education. To achieve this goal, the methodology was divided into two parts: a literature review of publications related to EE in the early years, and a pedagogical intervention research project conducted with a teacher and her third-grade students at a public school in Santa Maria, RS. The literature review covered publications from 2012 to 2022 and yielded seven relevant articles, which were categorized as follows: Teacher training in EE and Reports of Experiences in EE are analyzed using the ATLAS.ti software. The analysis is based on the Thematic Analysis between the indicators of pedagogical innovation and the categories created. As a second step, linked to pedagogical intervention research, we investigated the environmental perceptions of the teacher responsible for the class of students who participated in the research. This was based on the analysis of a fanzine prepared on the subject and analyzed in the light of DataBased Theory. The text is already well-written and adheres to the desired characteristics. No changes are necessary. Regarding the intervention methodology, it provided “criticalinnovative” EE for both the teacher and students in the participating class through creative and engaging activities. These activities helped to re-signify the school environment and foster a sense of environmental belonging. Additionally, this dissertation discusses the creation of student-produced fanzines resulting from the pedagogical intervention. The children created a total of 22 fanzines, and the process respected their autonomy and freedom of expression, giving them a leading role during the intervention.